Risk of gastrointestinal toxicities with PD-1 inhibitors in cancer patients: A meta-analysis of randomized clinical trials. Issue 48 (December 2017) - Wei, Wei; Luo, Zhibin
Abstract: Background: Anti-programmed cell death protein 1 (PD-1) antibodies have demonstrated significant clinical activity in many cancer entities. Gastrointestinal toxicities are one of its major side effects, but the overall risks have not been systematically evaluated. Thus, the purpose of this study was to evaluate the incidence and risk of gastrointestinal toxicities with PD-1 inhibitors in cancer patients through a meta-analysis. Methods: Eligible studies were searched for in PubMed, Embase, and the Cochrane Library. We included randomized controlled trials with cancer patients treated with PD-1 inhibitors with adequate data on gastrointestinal adverse events. Results: A total of 14 randomized controlled trials involving 7508 patients met eligibility criteria for this meta-analysis. The relative risk of all-grade diarrhea and colitis was 0.66 (95% confidence interval (CI): [0.50, 0.87]; P  = .003) and 3.36 (95% CI: [1.25, 9.04]; P  = .02), respectively. The relative risk of high-grade diarrhea and colitis was 0.58 (95% CI: [0.30, 1.11]; P  = .10) and 4.31 (95% CI: [1.11, 16.79]; P  = .04), respectively. Compared with ipilimumab alone, the nivolumab/ipilimumab combination was associated with a higher risk of developing all-grade diarrhea. Additionally, PD-1 inhibitor monotherapy resulted in a lower risk of developing gastrointestinal adverse events compared with ipilimumab alone. Conclusions: Our meta-analysis has demonstrated that the use of PD-1 inhibitors is associated with an increased risk of colitis compared with chemotherapy or everolimus.